CFD analysis in investigating the impact of turbine blade number on the performance of hydro turbine - Fatahul Arifin; Ade Putra Maulana; Indrayani Indrayani (Jurnal POLIMESIN, 2023)
The demand for electrical energy in Indonesia is growing, and therefore more effort is required to fulfill this need. Indonesia has considerable hydropower potential due to its geographical location and climate, by utilizing areas that have this potential to support the government's renewable energy program to provide electricity to the community. Impeller turbines are one option in an effort to create renewable energy generation. In this study, a comparison of the number of turbine blades was carried out using the Computational Fluid Dynamics (CFD) method, three models are 11, 13, and 15 blade impeller turbines designed at water with a runner diameter of 200 mm, blade thickness of 2 mm and an angle of 30 degrees then simulated using Comsol Multiphysics against different water flow rates. The simulation results show that the 11-bladed turbine model I has better performance because it has a lower pressure value but has a better velocity value compared to the two models simulated